Implementasi Pendidikan Holistik Islami Pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Muhammadiyah Bojong Gede Bogor - Amriah Malili; Yanti Hasbian Setiawati; Amie Primarnie (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to examine and analyze the implementation of the Islamic holistic education paradigm in Bojong Gede Muhammadiyah Elementary School Bogor. The research method uses qualitative research based on qualitative paradigms, strategies, and model implementations. Qualitative research aims to gain a general understanding of social reality from the participant's perspective. Sources of data in this study are words, actions, and written sources. Respondents in the study were principals, teachers and students of the Bojong Gede Muhammadiyah Elementary School, Bogor. Data were collected in three ways, namely: in-depth interviews (indept interview), observation (observation), review of documentation. Data analysis was carried out through inductive analysis, then formulating meaning on the basis of the analysis to the next response to find the theme. The results showed that Islamic holistic education in Islamic Religious Education learning at Muhammadiyah Elementary School Bojong Gede Bogor can help students develop: intellectual intelligence, spiritual intelligence, emotional intelligence and physical intelligence. Developing intellectual intelligence includes developing an honest, consistent, and open attitude. Developing intellectual intelligence includes developing rational thinking skills and acting rationally in accordance with the goals to be achieved. Developing emotional intelligence includes developing the ability to recognize one's own feelings and the feelings of others, the ability to motivate oneself and the ability to manage emotions. Developing physical strength includes developing skills to apply Islamic teachings which require eating and drinking nutritious, thayyib, and halal food. The implementation of Islamic holistic education is carried out by applying cooperative learning teaching methods, presentation methods and simulation methods. Conclusion; implementation of the holistic education paradigm in learning Islamic Religious Education plays a role in developing: intellectual intelligence, spiritual intelligence, and emotional intelligence and physical strength of students through learning interactions. Keywords: Learning, Islamic Religious Education, Holistic Education